2011
DOI: 10.4014/jmb.1107.07009
|View full text |Cite
|
Sign up to set email alerts
|

A TaqMan Real-Time PCR Assay for Quantifying Type III Hepatopancreatic Parvovirus Infections in Wild Broodstocks and Hatchery-Reared Postlarvae of Fenneropenaeus chinensis in Korea

Abstract: A highly sensitive and specific TaqMan real-time PCR was used to quantify hepatopancreatic parvovirus (HPV) type III infections in wild broodstocks and hatcheryreared postlarvae (PL) of Fenneropenaeus chinensis. Totals of 159 and 162 wild brooders from three locations were captured, and 140 and 180 PL were obtained from seven and six commercial hatcheries in 2007 and 2008, respectively. Among the three wild broodstock groups from 2007, only 1 group showed HPV infection and 3.2% of 159 brooders were positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In South Korea, two native penaeids, Fenneropenaeus chinensis (Osbeck, 1765) and Marsupenaeus japonicus (Bate, 1888), and an introduced species, Litopenaeus vannamei (Boone, 1931), are currently cultured, and the majority of the farmed production is derived from L. vannamei (Jang et al, 2009). Shrimp are one of the most economically important aquaculture species in Korea and worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In South Korea, two native penaeids, Fenneropenaeus chinensis (Osbeck, 1765) and Marsupenaeus japonicus (Bate, 1888), and an introduced species, Litopenaeus vannamei (Boone, 1931), are currently cultured, and the majority of the farmed production is derived from L. vannamei (Jang et al, 2009). Shrimp are one of the most economically important aquaculture species in Korea and worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Shrimp are one of the most economically important aquaculture species in Korea and worldwide. However, the farmed production of shrimp has been largely influenced by pathogens including white spot syndrome virus (WSSV) in Korea (Meng et al, 2010;Jang et al, 2011). For example, 32.9% of 468 shrimp farms in South Korea collapsed as a consequence of the WSSV outbreak in 2006, although production has recovered since then (Jang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its worldwide distribution, including the Asia-Pacific region, HPV has not been regarded as a major shrimp pathogen, probably because of heavy infection and severe economic losses caused by WSSV. However, recent real-time PCR surveys of shrimp tissue and seawater sampled from culture ponds of F. chinensis and L. vannamei showed high incidence rates of HPV in Korea [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Three genotypes of HPV have been reported to date, and in situ hybridization and nucleotide sequence analysis showed that the HPV strain from Korea belongs to genotype I [27,37]. However, recent PCR analysis of shrimp showing HPV symptoms failed to produce any amplification product using a type I-specific 1120F/1120R primer set [11,25]. HPV isolates from different hosts or geographical regions are known to show genetic differences [37].…”
Section: Discussionmentioning
confidence: 99%